THE DEVELOPMENT OF TOURIST ATTRACTIONS, FACILITIES AND QUALITY OF SERVICE TO VISITOR SATISFACTION IN RAGUNAN WILDLIFE PARK - Tiara Dita Puspita; Dimas Putra) Dedityatama (Jurnal Inovasi Penelitian, 2022)
This research is supported by the high tourism growth rate in Jakarta which is not matched by the increasing number of peaking tourists. The problem in this study is "what is the development of tourist attractions, facilities and service quality on visitor satisfaction at the Ragunan Wildlife Park, Jakarta. In particular, the focus is on the level of three variables, namely the development of tourism objects, facilities and service quality. After conducting a literature review and periodical preparation, the data that was collected was through a direct survey at the Ragunan Wildlife Park, Jakarta. Then the analysis of the data collected was obtained using multiple regression analysis. This analysis includes: the validity and reliability of the classical assumption test, multiple regression analysis, hypothesis testing through t and F tests, and analysis of the coefficient of determination . The F test shows that the tourist attraction variable has a significant effect on visitor satisfaction and other variables only have a positive and insignificant effect on visitor satisfaction. The Adjusted R square figure of 0.15 indicates that 15 percent of the visitor satisfaction variable can be explained through the three independent variables in the regression equation. While the remaining 85 percent is explained by other variables outside the three variables used in this study